Content comparison of unmet needs self‐report measures used in patients with head and neck cancer: A systematic review. Issue 12 (6th November 2019) - Shunmugasundaram, Chindhu; Rutherford, Claudia; Butow, Phyllis N.; Sundaresan, Puma; Dhillon, Haryana M.
Abstract: Objective: Morbidity from head and neck cancers (HNCs) and their treatment are significant, given their proximity to anatomical sites impacting facial appearance and function. Assessing the needs of HNC patients throughout their cancer journey is critical to informing quality care and improving quality of life. We aimed to identify available unmet needs measures in the HNC setting and appraise their content and psychometric properties. Methods: We conducted a systematic search of five electronic databases (July 2007‐July 2019) to identify studies of unmet needs in patients with HNC. In addition, three web‐based patient‐reported outcome measures (PROMs) databases were searched for unmet needs measures. Citations were screened for eligibility and identified measures reviewed for content coverage and psychometric properties. From identified measures and literature, a conceptual framework with 12 clinically relevant aspects of unmet needs was developed and used to assess the conceptual coverage of available unmet needs measures. Results: Literature search identified 273 records of which 28 studies assessing unmet needs in HNC cancer met eligibility criteria. Seven unmet needs measures were identified from retrieved studies and seven additional measures from PROM databases. Thus, 14 measures in total were reviewed. Content mapping revealed that three measures demonstrated excellent content validity (greater than 80% conceptual coverage): Patient Concerns Inventory (PCI), Needs Assessment for Advanced Cancer Patients (NA‐ACP), and James Supportive Care Screening (JSCS). Conclusion: We recommend PCI be used to measure unmet needs in the HNC setting considering the importance of content validity over quantitative psychometric properties.